Cancer families: what risks are they given and do the risks affect management?. Issue 12 (December 1996) - Rosser, E M; Hurst, J A; Chapman, C J
Abstract : The numbers of referrals to genetics clinics for people with a family history of cancer is increasing rapidly. Although it is likely that presymptomatic testing will soon be available for some families, for the majority of people with a family history of malignancy, risk can only be assessed by examining their pedigrees and referring to standard texts. In order to find out if clinical geneticists are providing consistent risks and suggestions for management we surveyed consultant clinical geneticists with a questionnaire about four people with a family history of malignancy. The clinical geneticists replying to our questionnaire gave consistent advice for the person with a family history of colon cancer, but there was wide variation in suggested risks and management for those with family histories of breast and multisite cancers. This survey shows that deciding on appropriate management for cancer families can be difficult and that there is uncertainty about the most effective methods of screening young people at high risk of developing cancers. However, it is important to provide consistent advice in order to evaluate screening protocols and lack of consistency in advice given to different family members can cause anxiety and distress. Consistency may be achieved by the use of one model for risk calculation, and by representatives from several specialties, such as surgery, radiology, genetics, and public health working together in order to coordinate local and national screening policies.